1994
DOI: 10.1159/000284887
|View full text |Cite
|
Sign up to set email alerts
|

The Season of Birth of Schizophrenics and Schizoaffectives

Abstract: We examined the birth distribution of 2,450 schizophrenic and 682 schizoaffective patients first admitted between 1971 and 1992 to the University Hospital for Psychiatry in Vienna. Our data showed an excess of schizophrenic births in the first quarter of the year and a deficit in the third quarter compared with expectation from census data. The quarterly distribution of schizophrenic births seemed to be different from the one of the schizoaffective patients. In schizoaffectives an excess of births in the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Our definition of schizophrenia included schizophreniform and schizoaffective disorders. However, previous studies have found similar seasonal variation in schizophrenia and schizoaffective disorder (Aschauer et al 1994 ;Torrey et al 1996). Thus, the broad definition is unlikely to be a major confounding factor.…”
Section: Limitationsmentioning
confidence: 78%
“…Our definition of schizophrenia included schizophreniform and schizoaffective disorders. However, previous studies have found similar seasonal variation in schizophrenia and schizoaffective disorder (Aschauer et al 1994 ;Torrey et al 1996). Thus, the broad definition is unlikely to be a major confounding factor.…”
Section: Limitationsmentioning
confidence: 78%
“…In the current literature, season of birth has so far been at the center o f interest in schizophren ic psychoses [12,[24][25][26], However, seasonality has been only tentatively considered to have a course-determining effect on schizophrenia. With respect to the manifestation seasonality o f subtypes, to our knowledge no studies have been carried out as yet.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 displays the recruitment of the study sample. The study is based on a computer list of subjects (n=729), born between 1960 and 1971, who had been hospitalized at the University Hospital for Psychiatry, Vienna and had received a clinical diagnosis of schizophrenia (295.0±6, 295.8±9), schizoaffective disorder (295.7) or affective disorder (296.0±9) according to ICD-9 criteria assigned at discharge from the hospital between 1978 and 1992 (14). Of those patients, 40 had been seen at the University Hospital for Child and Adolescent Neuropsychiatry, Vienna, prior to their ®rst hospital admission in adulthood and received IQ assessment during this initial presentation.…”
Section: Subjectsmentioning
confidence: 99%